Clinical assessment of rosacea severity: oriental score vs. quantitative assessment method with imaging and biomedical tools. Issue 2 (12th August 2016) - Kim, J.; Ahn, J. W.; Ha, S.; Kwon, S. H.; Lee, O.; Oh, C.
Abstract : Background: Rosacea is a common chronic inflammatory disorder affecting facial skin. Currently, no accurate and objective method is available for assessing the severity of rosacea. Most studies use the National Rosacea Society Standard (NRSS) grading method, which lacks objectivity and yields varying results. Methods: Eighteen patients with rosacea were included. Clinical severity was assessed on the basis of the NRSS grade, Investigators' Global Assessment, Patients' Global Assessment, and Dermatology Quality of Life Index. A skin color analysis system was used to measure the facial area showing erythema, and biophysical parameters of facial skin (transepidermal water loss and skin surface hydration) were examined. To find statistical significant in classification severity of the rosacea, statistical analysis was performed with all parameters. Results: A significant correlation ( P < 0.05) was found between the NRSS grade, facial area showing erythema, and biophysical parameters. The latter two factors differed significantly among patients with rosacea of different levels of severity (mild, moderate, severe; P < 0.05). Conclusion: Color imaging systems can be useful and reliable for evaluating the severity of rosacea, in addition to biophysical parameter assessment. The combination of these two analytical methods enabled objective and quantitative evaluation of the severity of rosacea.